Il ruolo delle Osservazioni della Terra dallo spazio nelle emergenze ambientali - Inghilesi, Roberto (GEOmedia, 2023)
Some environmental critical situations such as air and water pollution, forest fires and exceptional Mediterranean cyclones are presented to highlight the importance of Earth Observation (EO) techniques for environmental protection and monitoring. Methods based on EO and the use of machine learning techniques for land, marine and air quality observations are operationally implemented by the CSA (Centro operativo di Sorveglianza Ambientale) at ISPRA (Istituto Superiore per la Protezione e la Ricerca Ambientale) to provide support for environmental protection and in the event of environmental crisis or emergency.